REFLECTION OF FEMINITIVES IN VASYL STEFANYK WORKS - Brus, M. P. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article analyzes feminitives (appeals and women’s nicknames) which found reflection in Vasyl Stefanyk’s works. Special attention is paid to the specific features of the literary language of the author, a reperesentative of Pokuttya vernacular. Semantic, wordbuilding and stylistic peculiarities of names of women fixed in his literary works have been revealed. It has been pointed out that the feminicon of Vasyl Stefanyk’s literary works presents an effective combunation of general literary Western Ukrainian as well as Pokuttya lexical units in which Pokuttya colloquial elements prevail in forming the feminicon the short-story writer’s language.